Factors Affecting Efficient Export Documentation of Automobile and Parts Exporters - Maneekool, Chatrpol (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
This research aimed to 1) compare the efficient export documentation by automobile and parts exporters’ personal factors and 2) study capability of personnel, continuous process improvement, coordination with customers, information system, and quality of the service provider that affected the efficient export documentation. The questionnaires content validity of each question by Index of Item Objective Congruence (IOC), which valued between 0.67-1.00. Reliability of the questions of each variable was examined by Cronbach’s Alpha Coefficient, which valued between 0.81-0.94 used to collect data from 191 samples who were the exporters of automobile and parts. Data analysis using statistics, mean, standard deviation, t–test, one way ANOVA and multiple regression analysis. The research findings show that the different personal factors, which were gender, age, levels of education, positions, and experience of personnel had the different efficiency of export documentation at the significant level of .05. The information system (β=0.563), capability of personnel (β=.247), and coordination with customers (β=.153) affected the efficient export documentation at the significant level of 0.001. The continuous process improvement affected the efficient export documentation (β=.105) at the significant level of 0.01, respectively, (R2=0.847). The exporters should provide information system to increase accuracy and speed of export documentation, and support more training on export documents for the personnel in order to achieve more efficient export documentation.